Adsorption mechanism of shell powders on heavy metal ions Pb2+/Cd2+ and the purification efficiency for contaminated soils - Bai, Bing; Bai, Fan; Sun, Chenmiao; Nie, Qingke; Sun, Shuo (Frontiers in Earth Science, 2023)
The adsorption capacity of oyster shell powders (SPs) and the adsorption mechanism of heavy metal ions (HMs; i.e., cadmium ions Cd2+ and lead ions Pb2+) on SPs are discussed by means of adsorption kinetics tests, adsorption-desorption tests, scanning electron microscopy and Fourier transform infrared spectroscopy. The influences of seepage velocity, heavy metal types, and SP addition amount/concentration on the adsorption effect of SPs in the treatment of HMs in laterite as well as quartz sand were analyzed. Studies have shown that (i) the adsorption of HMs on SPs can be divided into three stages., i.e., the surface adsorption stage, the internal pore diffusion stage, and the equilibrium stage; (ii) with the increase in seepage velocity, the effluent concentration of HMs will slightly increase, and the residual amounts at each section of the column generally decrease rapidly with the increase in migration distance; (iii) the increase in the concentration of SP solution provides more adsorption points for the adsorption of HMs, and finally, the amount of HMs desorbed from quartz sand is reduced, which also reduces the concentration of HMs in the effluent. Overall, SPs possess high purification efficiency for the HMs of contaminated soils.